Separation and Analysis of Seven Kind Compounds in Three Medicine Herbs Extraction by RP-HPLC - Lee, K.J.; Kim, T.; Gu, M.J.; Lee, J.H.; Kim, H.K.; Ma, J.Y. (Asian Journal of Chemistry, 2014)
Saururus chinensis, Polygalae radix and Curcuma longa are widely known as traditional oriental medicinal herbs with various pharmacological activities. These three herbs were efficiently identified with 60 % aqueous ethanol and then successively partitioned with hexane, dichloromethane, ethyl acetate, normal butyl alcohol and water to investigate the seven compounds rutin, quercitrin, quercetin, onjisaponin B, bisdemethoxycurcumin, demethoxycurcumin and curcumin. The samples of these medicine herbs were simultaneously separated and analyzed by commercial C18 reverse phase high-performance liquid chromatography using the combination of water/trifluoroacetic acid and acetonitrile as the mobile phase in the isocratic and gradient elution mode. The analysis conditions were as follows: flow rate 1 mL/min, injection volume 10 μL and column oven temperature 40 °C at 200-400 nm wavelengths. The yield (%) and total extraction amount (mg) of n-BuOH (11.88-18.80 %, 1.2-9.4 mg) were higher than those of the other partition solvents hexane, dichloromethane and ethyl acetate. Also, the optimum mobile phase was simultaneously separated and analyzed. These results suggest that the extracts of these three medicinal herbs can be good therapeutic materials for anti-oxidant and anti-angiogenesis activities in the treatment of obesity.